Análise das Efetividades Sociais do Programa Nacional de Alimentação Escolar (PNAE) em Municípios Goianos: Inclusão Social e Formas Espúrias - De Souza, Rosana Machado; De Moraes Camargo Almeida, Luiz Manoel [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2017)
This paper discusses the social effectiveness of the PNAE in the municipalities of Anápolis-GO and Jaraguá-GO for family farmers from the point of view of food security elements treated in a broad way. Comparability became analytically important by the presence of a dynamic actor in the food safety network in Jaraguá-GO. The Brazilian Food Insecurity Scale (EBIA) was used as a method to measure household food situation, aiming to capture different dimensions of Food Insecurity (AI) and methods and instruments already used in other studies (Segall-Corrêa & Marin-Leon 2009; Almeida et al. 2015). In this paper, we present the socioeconomic, environmental, and dietary indicators that characterize the FNS of family farmers. The main hypothesis is that the forms of social organization of family farmers in Jaraguá-GO cooperative promoted the social inclusion of these families when accessing the institutional market of PNAE and effectively compose the public policy agenda, in contrast, the municipality of Anápolis- GO acquires its products from a cooperative located in Goiânia-GO, which does not guarantee food security from the axes of authenticity and solidarity and has been characterized as a spurious form.
Analysis of the Social Effectives of the National School Food Program (PNAE) in Goian Municipalities: Social Inclusion and Spiritual Forms
Keywords: Cooperatives; Family Farmers; Food Security; National School Feeding Program; Public Policies